Penerapan Teknik Marmet Untuk Meningkatkan Dan Memperlancar Produksi ASI Pada Ibu Post Partum Di Ruang Ponek RSUD dr. Soeratno Gemolong - Nur Aini Maulida Sareng; Irma Mustika Sari; Fitria Purnamawati (JURNAL RISET RUMPUN ILMU KESEHATAN, 2023)
Background;The post partum period is the period passed by mother giving birth starting from the first day of the birth to 6 weeks of birth. In this period every mother gives birth obliged to give her baby exclusive milk, sufficient amounts of breast milk are the best food for babies and can meet their nutritional needs for the first 6 months and thus reach optimum growth. The world’s exclusive coverage is 41% whereas the world’s exclusive who breast fund target is 70% and the coverage rate for breastfeeding in Indonesia is 37.7% in Central Java Province in 2018 in infants aged 0-6 months of 32.7%, the data is still below the national target of exclusive breastfeeding, which is 80%, so management is needed to assist post partum mothers in expressing breast milk more effectively, namely by using the guinea pig technique Objective; This application aims to know the effects of marmet technique to improve and promote breastfeeding production for the post partum in RSUD Dr.Soeratno Gemolong Method; this implemention use case studies Results; this implemention shows the results of breastfeeding post partum with 1 day intervension, 3 times treatmen and 15 minutes duration, suggests that marmet techniques that could solve the breastfeeding problems. Summary; there are differences in development before and after being given the guinea pig technique in post partum mothers